Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1164/ajrccm.153.6.8665043
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic response and lung distribution of lavage versus bolus Exosurf in piglets with acute lung injury.

Abstract: Despite evidence of surfactant dysfunction in the acute respiratory distress syndrome (ARDS), treatment with exogenous surfactant remains experimental. Uneven pulmonary distribution is one factor that may limit response. We investigated whether exogenous surfactant administered by lavage, consisting of a 35 ml/kg volume instilled by gravity and followed immediately by passive drainage (LAVAGE), would result in better lung distribution and physiologic response than with surfactant administered as a 5 ml/kg bolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 18 publications
1
16
0
2
Order By: Relevance
“…The advantages of the lavage technique could also help explain the unexpected beneficial effects in the E-LAVAGE group, confirming our previous experience with lavage Exosurf [2,3]. This non-protein-containing surfactant preparation has not been shown to be as effective as protein-containing surfactants such as 2 Survanta and Infasurf [7,15].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The advantages of the lavage technique could also help explain the unexpected beneficial effects in the E-LAVAGE group, confirming our previous experience with lavage Exosurf [2,3]. This non-protein-containing surfactant preparation has not been shown to be as effective as protein-containing surfactants such as 2 Survanta and Infasurf [7,15].…”
Section: Discussionsupporting
confidence: 69%
“…In the past 10 years, several investigators [6,11,18,25,27], including our group [2,3] have reported on a new administration technique for surfactant called "lavage administration." Unfortunately, there are significant differences in the administration technique amongst the studies.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, instilled surfactant volume impacts intrapulmonary drug distribution, which is already compromised by edema and inflammation as noted earlier. Studies in animal models of ALI/ARDS have indicated that the distribution of exogenous surfactant can be improved by instilling larger fluid volumes or utilizing associated bronchoalveolar lavage [151][152][153][154], but the feasibility and/or utility of these approaches in clinical practice is uncertain. Clinical studies on intratracheal or bronchoscopic instillation of exogenous surfactants in patients with ALI/ARDS have used a range of instilled volumes, with doses as high as 300 mg/kg [155] and as low as 25 mg/kg [26].…”
Section: Delivery Methods and Dosages For Exogenous Surfactant Therapmentioning
confidence: 99%
“…Both of these techniques have been shown to have a diminished ability to deliver surfactant uniformly when lung injury is nonhomogenous, as evident in the early stages of ARDS [18,[24][25][26]. Another novel method of surfactant delivery is by lavage administration [5,6,9,30,35,37]. Coined 'surfactant lavage,' it is characterized by delivering large dilute volumes of surfactant into the lungs followed by immediate drainage.…”
Section: Introductionmentioning
confidence: 99%
“…Coined 'surfactant lavage,' it is characterized by delivering large dilute volumes of surfactant into the lungs followed by immediate drainage. This method has shown promising results in delivering surfactant uniformly, removing alveolar proteins, and improving pulmonary function [5,6,30].…”
Section: Introductionmentioning
confidence: 99%